Neutrophil-to-lymphocyte ratio an inflammatory biomarker, and prognostic marker in heart failure, cardiovascular disease and chronic inflammatory diseases: New insights for a potential predictor of anti-cytokine therapy responsiveness - García-Escobar, Artemio; Vera-Vera, Silvio; Tébar-Márquez, Daniel; Rivero-Santana, Borja; Jurado-Román, Alfonso; Jiménez-Valero, Santiago; Galeote, Guillermo; Cabrera, José-Ángel; Moreno, Raúl (Microvascular research, 2023)
In the 20th century, research focused on cholesterol and lipoproteins as the key mechanism in establishing atherosclerotic cardiovascular disease (ASCVD). Given that some studies demonstrated subclinical atherosclerosis in subjects without conventional cardiovascular risk factors, the elevated low-density lipoprotein (LDL) levels alone cannot account for the entire burden of atherosclerosis. Hence, large-scale clinical trials demonstrated the operation of immune and inflammatory pathways in ASCVD. In this regard, the evidence establishes that cells of the immune system, both the innate (neutrophils, macrophages) and adaptive (T cell and other lymphocytes) limbs, contribute to atherosclerosis and atherothrombosis. Besides, basic science studies have identified proatherogenic cytokines such as interleukin (IL)-1, IL-12, and IL-18. In this regard, some studies showed that antiinflammatory therapy targeting the immune system by modulating or blocking interleukins, also known as anti-cytokine therapy, can reduce the risk of major cardiovascular adverse events. The neutrophils play a key role in the innate immune system, representing the acute phase of an inflammatory response. In contrast, lymphocytes represent the adaptive immune system and promote the induction of autoimmune inflammation, especially in the chronic inflammatory response. Through the literature review, we will highlight the inflammatory pathway for the physiopathology of ASCVD, HF, and COVID-19. In this regard, the neutrophil-to-lymphocyte ratio (NLR) integrates the innate immune and adaptive immune systems, making the NLR a biomarker of inflammation. In addition, we provided an update on the evidence showing that high NLR is associated with worse prognosis in heart failure (HF), ASCVD, and COVID-19, as well as their clinical applications showing that the normalization of NLR after anti-cytokine therapy is a potential predictor of therapy responsiveness and is associated with reduction of major adverse cardiovascular events. [Display omitted] •Current evidence supports the operation of the immune system and inflammatory pathways in atherosclerotic disease.•High neutrophil-lymphocyte ratio (NLR) is associated with a greater inflammatory response and is a prognostic marker.•Antiinflammatory therapy targeting the immune reduces cardiovascular events in patients with atherosclerotic disease.•A high NLR is a potential marker to select the appropriate candidates that may benefit from anti-cytokine therapy.•Normal NLR after anti-cytokine therapy is a predictor of therapy responsiveness in atherosclerotic and inflammatory diseases.